IMPLEMENTASI PBL (PROBLEM BASED LEARNING) BERBANTUAN MEDIA VIDEO SEBAGAI UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI SISTEM KOORDINASI KELAS XI SMA - Nurika Fitriana; Fida Rachmadiarti; Suyono Suyono (LPPM Institut Pendidikan Nusantara Global, 2023)
The teacher's ability to manage the class, specifically in the choice and use of learning models and media, is one of the causes of low motivation and poor learning results among students. Through the use of the problem-based learning approach and video media, this study seeks to improve the motivation and academic performance of class XI high school students. Class action research (PTK), which is conducted in two cycles with phases of planning, implementation, observation, and reflection, is this sort of study. The proportion of learning motivation was measured using the angket non-test method, and the results for cognitive learning were measured using the daily repetition test method with 35 students in high school's 11th grade. In the first cycle, the student participants' implementation of learning using the problem-based learning model and the motivational learning activity resulted in a score of 76.6% with sufficient good criteria, and in the second cycle, participants who experienced improvement received a rating of 90.3% with excellent criteria. The percentage of learning motivation as measured by four factors, attention, relevance, condifence, and satisfaction was rated at 58.49% in cycle I with a fairly high criterion and increased to 73.28% in cycle II. The cognitive learning outcomes of the students scored 65.71% in the first cycle of classical intensity and improved to 91.42% in the second cycle. The adoption of a learning model supported by video media can enhance the motivation and learning outcomes of students in grades XI high school, according to the research's findings.